CO2 Injection Study in Deltaic Reservoir System - Deraldy, Dave
At present, most of Indonesia’s oil field production has decreased significantly. Carbon dioxide (CO2) is one of the EOR methods that has been proven to improve the oil recovery factor. This study is performed in a deltaic system with lenses shaped reservoir at Mahakam Delta. A comprehensive literature study is performed to obtain data that correspond to the deltaic system. Data which required to make a model are reservoir pressure, fluid properties, and rock properties. The model used for the simulation is an oil reservoir that consists of one production well and two injection wells. CO2 Injection strategy is performed to maximize oil recovery in the model. From that data, CMG is used to perform sensitivity analysis in order to evaluate the effect of varying parameters on the reservoir performance. The effects of several flood design parameters on the simulation process were evaluated, such as pressure when the production well is shut in and the injection wells are operated, porosity, permeability, injection rate, area, and dip. The optimum value of the parameter is determined from the highest recovery factor. The time needed to reach minimum miscibility pressure (MMP) is 5-10 months .The simulation results demonstrated that the oil recovery from CO2 injection increased up to 50-60%. Predictive study is performed to compare the recovery factor of the model and the recovery factor by using the multi-regression method. The innovation of the proposed equation by multivariate regression method is in the ability to calculate the recovery factor of the CO2 injection in the deltaic system with the combination of the parameter value.